Measurement of the 236U(n,f) cross-section between 4 and 10 MeV with Micromegas detectors - Michalopoulou, V.; Diakaki, M.; Stamatopoulos, A.; Kalamara, A.; Kokkoris, M.; Lagoyannis, A.; Patronis, N.; Tsinganis, A.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
In this work, the measurement of the 236U(n,f) cross-section is presented, in the energy range 4 – 10 MeV, with the use of quasi-monoenergetic neutron beams produced via the 2H(d,n)3He reaction. The measurements took place at the neutron beam facility of the National Centre for Scientific Research ‘Demokritos’. The detection of the fission fragments was achieved with Micromegas detectors placed in a fission chamber, containing both the 236U targets and the reference samples, namely 238U and 235U. The analysis of the experimental data, as well as the first results will be presented.